Exploring the Effects of Sub-Dissociative Doses of Ketamine on Sedation Quality in Bronchoscopy: A Double-Blind Clinical Study - Hamidreza Shetabi; Samira Rostami (Archives of Anesthesia and Critical Care, 2024)
Background: Sedation is recommended during flexible fiberoptic bronchoscopy (FFB) to aid in airway evaluation, minimize patient mobility, and enhance patient safety. This study was conducted to compare the impact of different sub-dissociative ketamine (SDK) doses on the quality of sedation within FFB. Methods: This research utilized randomized clinical trial design involving three cohorts, each consisting of 30 participants. The cohorts were administered varying doses of ketamine: 0.2 mg/kg (SDK1), 0.4 mg/kg (SDK2), and 0.5 mg/kg (SDK3). After receiving ketamine, all participants received propofol in bolus dose 0.4 mg/kg followed by infusion 50-100 µg/kg. FFB started when sedation level 4 was reached, according to Ramsey's sedation score. Results: Regarding demographic variables revealed no statistically notable discrepancy among the cohorts (P>0.05). The SDK3 cohort exhibited a higher average sedation score and longer duration of sedation compared to the SDK2, with both metrics also surpassing those of the SDK1 cohort. (P>0.001). Furthermore, the satisfaction levels reported by the bronchoscopist (P=0.78) and the participants (P=0.019) were notably greater in the SDK3 cohort than in the other groups. Additionally, the amount of propofol administered to the SDK3 cohort was less than that given to the SDK2, and both cohort received lower doses than the SDK1 cohort (P>0.001). Conclusion: Elevating the SDK from 0.2 mg/kg to 0.5 mg/kg when administered alongside propofol correlates with a rise in the score of sedation, increasing patient and bronchoscopist satisfaction, and decreasing propofol consumption in FFB in adults. A dosage of 0.5 mg/kg might be more advantageous compared to alternative dosages for FFB in adult patients.